2018
DOI: 10.1093/jas/sky087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mn supplementation in late-gestating and lactating red deer (Cervus elaphus hispanicus) on milk production, milk composition, and calf growth

Abstract: This study describes the effects of Mn supplementation of 20 late-gestating and lactating Iberian red deer (Cervus elaphus hispanicus) females (hinds) fed a balanced diet on milk production and milk composition over the lactation period. Body weight of their calves at birth and at weaning was also evaluated. In addition, the effect of lactation stage was studied. For these purposes, 2 groups of hinds, one composed by 12 individuals (experimental) and the other by 8 individuals (control) were compared. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 43 publications
6
7
0
Order By: Relevance
“…Cappelli et al [9] concluded that Mn supplementation in deer fed a balanced diet increased impact energy and contents in minerals of antler bone tissue. Recently, Serrano et al [10] concluded that parenteral Mn supplementation of late-gestating and lactating hinds is recommended, even when they are fed a balanced diet, to increase milk production and content of fat, Ca, P, and Mn. This studied proved that parenteral Cu supplementation reduced SCC improving udder health and modifying the milk mineral profile which increased its content of Ca.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cappelli et al [9] concluded that Mn supplementation in deer fed a balanced diet increased impact energy and contents in minerals of antler bone tissue. Recently, Serrano et al [10] concluded that parenteral Mn supplementation of late-gestating and lactating hinds is recommended, even when they are fed a balanced diet, to increase milk production and content of fat, Ca, P, and Mn. This studied proved that parenteral Cu supplementation reduced SCC improving udder health and modifying the milk mineral profile which increased its content of Ca.…”
Section: Discussionmentioning
confidence: 99%
“…Copper supplemented (n = 9) and control (n = 8) Iberian red hinds were reared in captivity conditions and fed simulating the feeding system of deer farms using the same feeding program described by Serrano et al [10]. Briefly, hinds were kept in a 5000 m 2 open-door enclosure on an irrigated mixed pasture.…”
Section: Animals and Managementmentioning
confidence: 99%
See 3 more Smart Citations